1989
DOI: 10.1007/bf00445550
|View full text |Cite
|
Sign up to set email alerts
|

Chronic phosphatidylserine treatment improves spatial memory and passive avoidance in aged rats

Abstract: Learning/memory deficits in senescent animals are widely used as a tool to evaluate the therapeutic potential of agents for treatment of age-associated cognitive dysfunction. As assessed in the Morris water maze test, aged (21-24 months) rats showed a variable loss of spatial memory. Aged non-impaired rats performed as well as young subjects, while aged impaired rats exhibited a severe and persistent place-navigation deficit. Passive avoidance retention was similarly affected in the two aged subpopulations. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 32 publications
2
25
0
1
Order By: Relevance
“…Zanotti et al (16) reported that the intraperitoneal injection of BC-PS restored scopolamine-induced amnesia in rats, which seemed to offer a clue to the anti dementia mechanism of phosphatidylserine. Because scopolamine is an acetyl choline receptor antagonist, the results in Table 4 suggest that SB-tPS affects on brain acetylcholine metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Zanotti et al (16) reported that the intraperitoneal injection of BC-PS restored scopolamine-induced amnesia in rats, which seemed to offer a clue to the anti dementia mechanism of phosphatidylserine. Because scopolamine is an acetyl choline receptor antagonist, the results in Table 4 suggest that SB-tPS affects on brain acetylcholine metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…After Toffano and Bruni reported in 1980 that brain cortex phosphatidylserine (B-PS), a pharmacologically active phospholipid, counteracts age-related changes in the central nervous system (CNS) (1), many investigators have observed that exogenous B-PS affects neurotrans mission (2-4) and behavioral performance (5,6) by modifying the composition and function of the neuronal membrane, which is associated with aging (7). Clinical investigations have also shown that B-PS treatment can improve Alzheimer's disease (AD) and related cognitive disorders (8,9).…”
mentioning
confidence: 99%
“…Although there is as yet little direct evidence that SB-tPS involves central cholinergic mechanisms, these results suggest that the anti-amnesia effect of SB-tPS could be attributed to the activation of cholinergic neu ronal systems in the CNS. Indeed, regarding mechanism of B-PS, several investigators have proposed a cholinergic mechanism based on the findings that the acute adminis tration of B-PS antagonizes the amnesic effects of SCP on spontaneous alternation and passive avoidance (5,6).…”
mentioning
confidence: 99%
“…Also, other experiments have shown an improvement in memory, learning capacity, and other cognitive parameters in PS-supplemented rodents [7][8][9][10][11]. This is plausible, since PS was found to stimulate neurotransmitter release [7,12], increase brain glucose metabolism [13,14] and reduce oxidative stress in the brain [15].…”
Section: Phosphatidylserine (Ps) and Phosphatidic Acid (Pa) In Memorymentioning
confidence: 88%